Implementasi Penelitian Participatory Action Research Dalam Disiplin Keilmuan Desain Komunikasi Visual - Subudiartha, I Nyoman (CV Insan Kreasi Media, 2023)
Visual Communication Design is one of the design sciences that studies graphic processing procedures to convey messages visually. Visual Communication Design is also a major in tertiary institutions, both public and private. In Indonesia itself, the term DKV was popular in the 80s where DKV was popularized by Gert Dumbar. The aim this research is to find out whether PAR research can be used in the science of Visual Communication Design by giving examples of the application of PAR research in the science of Visual Communication Design. Like other lecture majors that are closely related to research, Visual Communication Design has many choices of research methods that can be used to research and design. One of the research methods that can be used in the science of Visual Communication Design is applied research or Participatory Action Research (PAR). This research is one of the qualitative research methods in which this research involves participation in its implementation. When Visual Communication Design is associated with Applied Research, the question arises whether Applied Research can be used in Visual Communication Design scholarship. By using a qualitative descriptive method, these two things become interesting topics to discuss. Through a qualitative descriptive method by collecting data through written sources in the form of books and online journals as well as describing and explaining the results of the research. After conducting research, the authors conclude that Applied Research can be used in Visual Communication Design science because there are other researchers who use this method.